Low Serum Cholinesterase Levels Predict Poor Prognosis in Patients with Ovarian Cancer - Su H; Liao D; Huang C; Liu Q; Yu L (International Journal of General Medicine)
Hailan Su,1,* Danfeng Liao,2,* Chaolin Huang,2 Qin Liu,3 Lingfang Yu1 1Department of Gynecology, Suzhou Ninth People’s Hospital, Suzhou, People’s Republic of China; 2Department of Gynecology and Obstetrics, The First Affiliated Hospital of Chengdu Medical College, Chengdu, People’s Republic of China; 3Department of Emergency Medicine, The First Affiliated Hospital of Chengdu Medical College, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingfang Yu, Department of Gynecology, Suzhou Ninth People’s Hospital, No. 2666, Ludang Road, Wujiang District, Suzhou City, Jiangsu Province, 215200, People’s Republic of China, Email yulingfang2024@163.com Qin Liu, Department of Emergency Medicine, The First Affiliated Hospital of Chengdu Medical College, No. 278, The Middle Section of Baoguang Avenue, Xindu District, Chengdu City, Sichuan Province, 610500, People’s Republic of China, Email 519791695@qq.comObjective: Previous studies reported that low cholinesterase (ChE) levels were associated with poor prognosis in various cancers, including bladder, pancreatic, lung, and colorectal cancers. This study aimed to evaluate the clinical significance of serum ChE levels as a prognostic biomarker in ovarian cancer.Materials and Methods: A retrospective cohort analysis was conducted on 168 patients diagnosed with epithelial ovarian cancer at the Suzhou Ninth People’s Hospital from 2019 to 2020. Serum ChE levels were measured before initiating treatment and stratified into low and high groups based on the median level (7600 U/L). Clinical and pathological data, such as FIGO stage, age, tumor histological type, and survival outcomes, were collected. Kaplan-Meier analysis and Cox proportional hazards regression were used to assess the relationship between ChE levels and overall survival and disease-free survival.Results: ChE levels were significantly correlated with clinicopathological features of epithelial ovarian cancer, including FIGO stage (p < 0.001), surgery completeness (p = 0.001), and platinum-resistant (p = 0.001). Kaplan-Meier analysis demonstrated that patients in the low ChE group had significantly worse overall survival (p = 0.003) and disease-free survival (p = 0.005) than those in the high ChE group. Multivariate Cox regression analysis identified low serum ChE levels as an independent predictor of poor overall survival and disease-free survival.Conclusion: Low serum ChE levels are independently associated with poor prognosis in ovarian cancer patients, reflecting systemic inflammation, malnutrition, and potential hepatic dysfunction. These findings suggest that ChE could serve as a cost-effective and non-invasive biomarker for risk stratification and prognosis in clinical practice.Keywords: cholinesterase, ovarian cancer, disease-free survival, overall survival